Contextualizing bilateral asymmetry and gender: A multivariate approach to femoral cross‐sectional geometry at rural Medieval Pieve di Pava, Italy. Issue 1 (30th September 2022) - Kinkopf, Katherine M.; Agarwal, Sabrina C.; Giuffra, Valentina; Minozzi, Simona; Campana, Stefano; Caramella, Davide; Riccomi, Giulia
Abstract: Objectives: Our objective was to identify the relationship between biocultural factors of sex‐gender and age and patterns of femoral cross‐sectional geometry with historical evidence about labor and activity from an archeological skeletal sample excavated from the rural Medieval site Pieve di Pava. Materials and Methods: The study site, Pieve di Pava, was a rural parish cemetery in Tuscany with osteoarcheological remains from the 7th to 12th centuries. Cross‐sectional geometric analysis of femora from 110 individuals dated to the 10th‐12th centuries were used to examine trends in bone quantity, shape, and bending strength between age and sex groups, as well as in clusters identified through Hierarchical Cluster Analysis (HCA). Results: Overall, our study sample showed remarkable heterogeneity and our cluster analysis revealed a complex underlying structure, indicating that divisions of labor did not follow a strict gender binary in our sample. We found high levels of bilateral asymmetry in our sample in multiple cross‐sectional areas for a significant proportion of the population. We found minimal differences between age groups or sex. Discussion: Our results suggest that males and females had varied experiences of labor and work during their lives that did not reflect the strict binary gender roles sometimes documented for medieval Europe. One important axis of difference is the direction and magnitude of bilateral asymmetry observed in our femur sample, which is associated with divergent trends in section moduli and bone area measures. Abstract : Medieval farmers (mixed gender) work alongside each other threshing spelt (Lombardia, c. 1390). Spelta [Manuscript]. Biblioteca Casanatense, Rome. Tacuinum Sanitatis MS 4182, f. 87.